68Ga-FAPI PET/CT versus 18F-FDG PET/CT: Differentiating Metastatic Disease and Reactive Lymph Nodes in a Case of Carcinoma of Breast/Acquired Immunodeficiency Syndrome - Gunasekaran, Gopinathraj; Amalachandran, Jaykanth (World Journal of Nuclear Medicine, 2024)
Gallium-68 (68Ga)-fibroblast activation protein inhibitor (FAPI) positron emission tomography (PET) images the cancer-associated fibroblast that forms a vital component of the tumor microenvironment. It is known that 68Ga-FAPI PET can aid in differentiating reactive lymph nodes from metastatic lymph nodes. 18F-fluorodeoxyglucose (FDG) PET/computed tomography (CT) is still the most commonly used PET radiopharmaceutical in the evaluation of a wide range of malignancies including breast carcinoma. Reactive lymph nodes may also show FDG uptake which can hinder optimal assessment for metastatic involvement. We report an interesting case of invasive ductal carcinoma of the right breast with associated World Health Organization clinical stage I acquired immunodeficiency syndrome for which 18F-FDG PET/CT and 68Ga-FAPI PET/CT were done.
Keywords: 68Ga-FAPI; reactive node; metastatic node; breast carcinoma; positron emission tomography; PET; acquired immunodeficiency syndrome